The association between leukocytes and sperm quality is concentration dependent - du Plessis Stefan S; Mahfouz Reda; Agarwal Ashok; Lackner Jakob E; Schatzl Georg (BMC, 2010)
Abstract Background To evaluate the association between leukocytes (polymorphonuclear granulocytes -PMNL) and semen parameters at different leukocyte concentrations. Methods This was a retrospective clinical study at a university hospital andrology clinic. Semen samples from infertile men were analyzed for sperm morphology and motility according to seminal leukocytes (PMNL) concentration (category A: >0 to <0.25 × 10(6)/mL; category B: >0.25 to <0.5 × 10(6)/mL; category C: >0.5 to <0.75 × 10(6)/mL; category D: >0.75 to <1.0 × 10(6)/mL, category E: >1 × 10(6)/mL). Results The percentage of sperm with normal morphology increased significantly from category A (14%) to category D (19%) but decreased in category E to levels (14%) similar to those in category A. Motility grades a and a+b (combined) also increased from category A (12%, 20%) to category D (18.0%, 28.5%) and decreased in category E (11%, 20.5%) to levels similar to those in category A. Sperm deformities and motility grades c and d increased progressively in all categories. Summary Leukocytes had a positive association with normal morphology and progressive motility in semen samples at a concentration of 0-1 × 10(6)/mL. The findings suggest that the association between leukocytes (PMNL) and semen quality might be concentration dependent.